Moderate Nitrogen Management Enhancing Maize Lodging Resistance by Reducing Pathogen Infection and Expansion of Stalk Rot - Mengjing Zheng; Lihua Lv; Yongzeng Cui; Yueling Shi; Jingting Zhang (Agronomy)
At present, maize production is facing the challenge of balancing stalk lodging caused by stalk rot with maintaining a good grain yield potential. Improving the basal internode properties by optimizing nitrogen (N) management is an effective strategy to reduce the stalk rot incidence and stalk lodging rate, whilst simultaneously achieving a stable grain yield. A two-year field study was conducted to evaluate the basal internode characteristics under natural field conditions and inoculation with Fusarium pseudograminearum, the causative pathogen of stalk rot, and also to measure the ultimate grain yield with four different N fertilizer application rates (0, 120, 180, and 240 kg N ha−1). Rapid injection inoculation and histochemical staining technologies were employed to assess the stalk rot and lodging resistance. The results showed that reducing N rates improved the basal internode qualities (i.e., shorter internode length, larger cross-sectional area, improved internode plumpness and sclerenchyma tissue, and higher lignified degree and vascular number in sclerenchyma tissue) and enhanced the infection resistance. The lodging rate and stalk rot incidence all gradually declined with reduced N rates. Furthermore, pathogen diffusion degree which was indicated by infection index was decreased with reducing N rates. Ultimately, the mechanical strength of the N0, N120, N180, and N240 plants decreased by 5.31%, 5.83%, 5.01%, and 11.21% compared with that of the control, respectively. These results suggested that the stalk quality was improved through optimal nitrogen application, and also that the stalk rot and lodging resistance increased. The grain yield of the N180 plants was superior to that of those receiving the other treatments. Overall, 180 kg N ha−1 is recommended to balance the stalk lodging resistance and grain yield in the research region. Additionally, breeding cultivars with improved stalk quality is likely to be required to counter the escalating lodging risks arising from stalk rot occurrence.